Strong size selectivity in the self-assembly of rounded nanocubes into 3D mesocrystals. Issue 7 (15th June 2020) - Josten, Elisabeth; Angst, Manuel; Glavic, Artur; Zakalek, Paul; Rücker, Ulrich; Seeck, Oliver H.; Kovács, András; Wetterskog, Erik; Kentzinger, Emmanuel; Dunin-Borkowski, Rafal E.; Bergström, Lennart; Brückel, Thomas
Abstract : Depth-resolved structural analysis reveals strong size selectivity of self-assembled iron oxide nanoparticles. Abstract : The self-assembly of nanoparticles into highly ordered crystals is largely influenced by variations in the size and shape of the constituent particles, with crystallization generally not observed if their polydispersity is too large. Here, we report on size selectivity in the self-assembly of rounded cubic maghemite nanoparticles into three-dimensional mesocrystals. Different X-ray scattering techniques are used to study and compare a nanoparticle dispersion that is used later for self-assembly, an ensemble of mesocrystals grown on a substrate, as well as an individual mesocrystal. The individual μm-sized mesocrystal is isolated using a focused-ion-beam-based technique and investigated by the diffraction of a micro-focused X-ray beam. Structural analysis reveals that individual mesocrystals have a drastically smaller size dispersity of nanoparticles than that in the initial dispersion, implying very strong size selectivity during self-assembly. The small size dispersity of the nanoparticles within individual mesocrystals is accompanied by a very narrow lattice parameter distribution. In contrast, the lattice parameter distribution within all mesocrystals of an ensemble is about four times wider than that of individual mesocrystals, indicating significant size fractionalization between mesocrystals during self-assembly. The small size dispersity within each mesocrystal has important implications for their physical properties.